Pengecatan Balai Pertemuan Kelurahan Muktiharjo Kidul Kecamatan Pedurungan Kota Semarang - Muhammad Afan Tri Junianto; Diah Rahmawati; Nurti Kusuma Anggraini (Jurnal Pengabdian KOLABORATIF, 2023)
Building maintenance is an activity to maintain the reliability of the building and its infrastructure and facilities so that the building is always fit for function. A consistent building maintenance period has become a requirement that must be met, especially for buildings that are used commercially. As one part of the construction process, post-construction building maintenance has an important role to ensure the life of building construction. Lack of understanding of work methods, procedures, standardization of maintenance, and equipment used for maintenance activities of building elements also affects the age of building construction. This activity aims to carry out building maintenance in the form of repainting the meeting hall building to provide comfort and safety for the community, both for housing or residence, religious activities, business activities, social and cultural activities, and other special activities. The method used is in the form of socialization and direct practice of painting meeting halls. The result of this community service activity is that it has finished repainting the meeting hall of the Muktiharjo Kidul Village, Pedurungan District, Semarang City so that it looks more beautiful and comfortable.